Comparison of the Traditional Games of Bentengan and Galah Asin on the Sportsmanship Attitude of Class IV SDN Panyingkiran I Students - Dede Triyana Saputra; Anin Rukmana; Yogi Akin (Journal of Physical Education and Sport Pedagogy, 2021)
The problem that arises in this study based on initial observations is the low sportsmanship among students, especially in traditional game activities. This is indicated by an attitude that does not want to accept defeat, which causes quarrels to arise. Apart from that, other problems also arise from the traditional games themselves, which children rarely play due to the development of technological knowledge. In solving these problems, the method used in this study is a Quasi Experiment with the research design of The Static Group Pretest-Postest. The sample in this study came from the fourth-grade students of SDN Panyingkiran I, totalling 28 students divided into 14 students in the Bentengan game experimental group and 14 students in the Galah Asin game experiment group with a research instrument in the form of a questionnaire with a Likert scale. Based on the results of the calculation of the two-party test, it shows that the value of Sig. (2-tailed) 0.009 0.05, which means that the traditional Galah Asin game is more influential than the traditional Bentengan game on the sportsmanship attitude of the fourthgrade students of SDN Panyingkiran I.